RELASI SINTAKSIS DALAM BAHASA ARAB: KAJIAN FUNGSI MUBTADAʼ, KHABAR, FĀʼIL, DAN MAFʼUL - Umroh Aidina; Hamzah (Universitas Muhammadiyah Makassar, 2026)
Abstract: Syntactic relations in Arabic constitute a fundamental dimension of Arabic grammar that determines the grammatical and semantic functions of each element within a sentence structure. This study aims to describe and analyze the syntactic functions of four primary relational categories: mubtadaʾ (subject of nominal sentence), khabar (predicate of nominal sentence), fāʾIl (agent of verbal sentence), and mafʿul (object of verbal sentence), with particular attention to their morphosyntactic marking, positional variation, and semantic roles. Employing a qualitative descriptive approach through content analysis of three selected corpora Quranic verses, classical Arabic prose, and contemporary Arabic academic texts this study analyzes 312 sentences utilizing distributional and referential methods. The results indicate that the four syntactic functions are systematically distinguished through case endings (iʿrāb), verb-argument agreement patterns, and clause-level positional constraints. The study also identifies complex interactions between nominal and verbal sentence types, including the phenomenon of mixed sentence patterns (jumlah ismiyyah with verbal khabar and jumlah fiʼliyyah with nominal fāʾIl constructions). These findings contribute theoretically to Arabic syntactic typology and carry pedagogical implications for Arabic grammar instruction at higher education levels. Keywords: Arabic Syntax; Mubtadaʾ; Khabar; FāʾIl; Mafʿul; Syntactic Relations